Climate Change and the Health Sector : Healing the World. - Thomas, Alexander; Reddy, K. Srinath; Alexander, Divya; Prabhakaran, Poornima (Milton : Taylor & Francis Group, 2021)
This volume positions the health sector as a leader in the fight against climate change and explores the role of the health system in climate policy action.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books